2019
DOI: 10.1007/s40201-019-00386-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to air pollutants and birth weight in Tehran, Iran

Abstract: Background Air pollution can cause various health outcomes, especially in susceptible groups including pregnant women. Low birth weight (LBW) is among the adverse birth outcomes and is one of the main causes of infant mortality. The aim of this study was to assess the association between air pollutants and LBW in Tehran, Iran. Methods In this case-control study, 2144 babies born in three hospitals of Tehran (Iran) during 2011 to 2012 whose mothers were the residents of this city in last 5 years were considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our results could benefit epidemiological studies of long-term exposure to nitrogen dioxides in the Middle Eastern megacity of Tehran. Examples of such epidemiological studies are the effect of long-term exposure to air pollutants on the incidence of lung cancer, the air pollutants' long-term effects on low birth weight, and the effect of exposure to long-term multiple pollutants on the incidence of leukemia [50][51][52]. Our long-term exposure model provided not just an updated estimate for the long-term exposure to nitrogen dioxide, but it also provides for the long-term means across all times of the day.…”
Section: Discussionmentioning
confidence: 99%
“…Our results could benefit epidemiological studies of long-term exposure to nitrogen dioxides in the Middle Eastern megacity of Tehran. Examples of such epidemiological studies are the effect of long-term exposure to air pollutants on the incidence of lung cancer, the air pollutants' long-term effects on low birth weight, and the effect of exposure to long-term multiple pollutants on the incidence of leukemia [50][51][52]. Our long-term exposure model provided not just an updated estimate for the long-term exposure to nitrogen dioxide, but it also provides for the long-term means across all times of the day.…”
Section: Discussionmentioning
confidence: 99%
“…In the modern lifestyle, about 90% of a lifetime, on average, spends indoors, and this considerable fact directs the researchers to the development of studies scoping indoor air quality as a crucial issue threatening human health and equipment [4][5][6][7]. There is clear scientific evidence that air pollution poses a significant risk to public health, particularly to vulnerable groups such as children, the elderly, and pregnant women [8,9]. The World Health Organization (WHO) reported that approximately 3.8 million premature deaths were attributed to indoor air pollution each year, and this number contributed to approximately 7.7% of annual mortality [10].…”
Section: Introductionmentioning
confidence: 99%